Fatal bleeding from gastric ulceration during first day of life–possible association with social stress. Issue 2 (February 1979) - Pugh, R J; Newton, R W; Piercy, D M
Abstract : Death from haemorrhage is described in a 21-hour-old baby boy with acute gastric ulceration. Particular note is made of the very high level of psychosocial maternal stress during the last trimester of pregnancy. A causal relationship of this stress and the peptic ulceration is suggested, with gastrin as the mediator.